2011
DOI: 10.1590/s0004-27492011000600007
|View full text |Cite
|
Sign up to set email alerts
|

Uso de ganciclovir 0,15% gel para tratamento de ceratoconjuntivite adenoviral

Abstract: Comitê de Ética em Pesquisa da UNIFESP/EPM -CEP 2042/08 RESUMOObjetivos: Determinar a efetividade e a toxicidade do ganciclovir 0,15% gel no tratamento de ceratoconjuntivites adenovirais e na prevenção de complicações tais como infiltrados corneanos, membranas ou pseudomembranas conjuntivais. Métodos: Ensaio clínico duplo-cego, intervencionista, randomizado. Os 33 pacientes com diagnóstico clínico de ceratoconjuntivite adenoviral com início dos sintomas há menos de cinco dias foram randomizados em dois grupos:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…One research group working in the cotton rat eye model reported that 3% GCV reduced Ad5 replication and pathology (23). In a published clinical study, treatment with 0.15% GCV ophthalmic gel improved the outcome of Ad conjunctivitis (49 In the present report, we have demonstrated that systemically administered GCV mitigates the effects of generalized Ad5 infection in immunosuppressed Syrian hamsters ( Fig. 1 and 2).…”
Section: Discussionsupporting
confidence: 63%
“…One research group working in the cotton rat eye model reported that 3% GCV reduced Ad5 replication and pathology (23). In a published clinical study, treatment with 0.15% GCV ophthalmic gel improved the outcome of Ad conjunctivitis (49 In the present report, we have demonstrated that systemically administered GCV mitigates the effects of generalized Ad5 infection in immunosuppressed Syrian hamsters ( Fig. 1 and 2).…”
Section: Discussionsupporting
confidence: 63%
“…In a double blind, interventional and randomized clinical trial [ 44 ], 33 individuals with adenoviral conjunctivitis who had symptoms for five days or fewer were randomly divided in two groups: group 1 (treatment) with 19 subjects using ganciclovir gel and group 2 (control) with 14 individuals treated with preservative free artificial tears. Group 1 showed a not statistically significant tendency of better and quicker answer in terms of signs and symptoms compared with group 2.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that GCV, the parental drug of VGCV, was active against Ad infection in hamsters, and there is anecdotal clinical evidence that GCV may be effective against Ad infection and pathogenesis in transplant patients [ 30 , 31 , 32 , 33 , 34 , 35 ]. In addition, treatment with 0.15% GCV ophthalmic gel improved the outcome of Ad conjunctivitis [ 36 ]. It seems reasonable that if GCV can be effective in the clinic, that VGCV should be effective as well.…”
Section: Discussionmentioning
confidence: 99%